Guanine nucleotides induce tyrosine phosphorylation and activation of the respiratory burst in neutrophils. - Nasmith, P E (1989)
Activation of the NADPH oxidase was examined in electrically permeabilized human neutrophils exposed to non-hydrolysable guanine nucleotides. Guanosine 5'-[gamma-thio]triphosphate (GTP[S]) induced a marked increase in the rate of O2 consumption, which was partially resistant to staurosporine, an inhibitor of protein kinase C, under conditions where the response to diacylglycerol was virtually abolished. The respiratory burst elicited by GTP[S] was dependent on the presence of ATP and Mg2+, suggesting involvement of phosphorylation reactions. Accordingly, phosphoprotein formation was greatly stimulated by the guanine nucleotide. The polypeptide phosphorylation pattern induced by GTP[S] was similar to, but not identical with, that observed with diacylglycerol, indicating the activation of kinases other than protein kinase C by the guanine nucleotide. The possible involvement of tyrosine kinases was assessed by immunoblotting using anti-phosphotyrosine antibodies. Treatment of electroporated cells with GTP[S] stimulated the accumulation of tyrosine-phosphorylated proteins. This effect was not induced by diacylglycerol, indicating that tyrosine phosphorylation is not secondary to stimulation of protein kinase C. The results indicate that, in neutrophils, activated G-proteins can stimulate tyrosine kinase and/or inhibit tyrosine phosphatase activity. Changes in the amounts of tyrosine-phosphorylated proteins may signal activation of the respiratory burst.